International Migration and Institutional Quality in the Home Country: It Matters Where You Go and How Long You Stay! - Ngoc Thi Minh Tran; Michael P. Cameron; Jacques Poot (Institute of Labor Economics (IZA), 2017)
International migrants are widely recognised as agents of institutional change in their home countries. However, the huge growth in temporary migration in recent years demands a fresh investigation of this phenomenon. Theoretically, a country's diaspora constitutes one of the four principal channels through which international migration may alter development. A core factor enabling the transnational influence of diasporas is their retained connection to home countries, which is plausibly contingent on the duration-of-stay in the host countries. This paper exploits the Database on Immigrants in OECD Countries to investigate the influence of diasporas living in OECD countries on institutional quality in their home countries, and takes into account the heterogeneity of diasporas' duration-of-stay composition. Instead of simply using immigrant numbers to measure the diaspora size, we calculate institutional-quality-adjusted immigrant stocks to allow for variations in institutional quality between host countries. Additionally, we utilize duration-of-stay in the host country as an indicator of the strength of interaction with the home country. Our cross-sectional and panel analyses find a significant positive impact of diasporas living in OECD countries on institutional quality in home countries. Remarkably, the diffusion of advanced institutions from developed host countries to home countries through the international migration channel is stronger with diasporas characterized by shorter duration-of-stay, i.e. with those who may be expected to still have stronger links with the home country.
Keywords: F22; O15; 330; institutional quality; international migration; diaspora; duration-of-stay